Control of drive system for car-like mobile platform - Mohd Syahidatul Naim Parmin
The objectice of this project is to get better knowledge about the microcontroller and the drive system for the stepper motor.To find the correct program base on waveform that we want so after that we can control the driver of stepper motor input and to setup a simple control unit circuit and test the circuit.